Frequency of Parallelism of Occlusal Plane to ALA-Tragus Line in Different age Groups: A Photographic Study - Najeeb Ullah, Abdul Mueed Zaigham, Samia Shafiq, Khalid Yaqub, Aleshba Saba Khan, Atiq-Ur-Rehman, Muhammad Sheraz Sadiq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: For the complete dentures to look, sound, fit, and feel their best, it is crucial that the occlusal plane be positioned correctly. There are a number of different anatomical landmarks that have been proposed to arbitrate the position of the occlusal plane, with the Ala-tragus line being the most commonly adopted by the professions. Purpose: To ascertain the effect of age on location of Ala-Tragus line. Materials and methods: One hundred and seventy six patients (128 males and 48 females) having complete dentition were recruited in the study, and grouped according to their age. Patients’ right lateral profiles were photographed after they had positioned the fox plane intraorally so that it was parallel to the occlusal plane. Images were taken with Canon camera model no. EOS 700 D with a resolution power of 18.0 Mega pixels, images produced were transferred to computer and traced using computer software AutoCAD 2014 and angle between Fox plane and superior, Middle and inferior borders of Ala-tragus and angle measured between three different lines. Data obtained was statistically analyzed using Pearson chi-square test. Results: There was a statistically significant relationship between age and Ala-Tragus line height. When the middle tragal border was used as the posterior reference point in the analysis, the occlusal plane was also shown to be more parallel to the Ala-tragus line age groups A, C, and D, being 42.0% (74/176). The second common location was the superior line in age groups B and D, being 36.9% (65/176), and the least common location was found to be the inferior line in almost all age groups, being 21.0% (37/176). Conclusion: Within the limitations of this study, it can be concluded that a definite relationship exists in between age and level of Ala-tragus line. Keywords: Ala-tragus line, interpupillary line, occlusal plane